Vodún, Globalization, and the Creative Layering of Belief in Southern Bénin - Landry, Timothy R. (Journal of religion in Africa, 2015)
This article examines the ways in which beliefs and forms of secret religious knowledge are (re)formed and mobilized creatively by Béninois practitioners of Vodún, who participate actively in Bénin’s changing religious landscape. This expansion, encouraged by contemporary trends in globalization and transnationalism such as spiritual tourism, modernity, and an increased Evangelical Christian presence in West Africa, has propelled belief into local and transnational discourse. While persuasive arguments have been made against the use of the term ‘belief’ to describe African religion, in this article I show how Vodún’s increased presence on the global stage and strategies employed by local practitioners to frame Vodún as transnational has once again made belief in African religion an important and meaningful point of critical analysis.